Fictitious pseudo Meig’s syndrome: A medical emergency - Shukla, S; Acharya, N; Acharya, S; Rajput, DP; Vagha, S (Journal of College of Medical Sciences-Nepal, 2012)
The present case scenario deals with an acute on chronic symptomatology, and collapsed state of the patient with poor vitals on admission in casualty. Clinical work up pointing to an elevated serum CA 125 levels and USG pelvis suggesting peritoneal adhesions with cystic to firm mass in left ovary and minimal free fluid in abdomen and cul de sac, X Ray chest suggesting right sided Pleural effusion. It was after careful evaluation of the case, with past and present history along with signs, symptommatology and intraoperative findings that differentials like Chronic granulomatous lesions, endometriosis, Neoplastic lesions with metastasis and Meig’s syndrome or Pseudo Meig’s were evaluated. Finally, a diagnosis of genital tuberculosis with enodmetriosis was confirmed on histopathological evaluation. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5975 JCMSN 2011; 7(1): 57-64